2020
DOI: 10.1016/j.molmet.2020.101038
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of the immune system in a brain-liver-fats organ network during short-term fasting

Abstract: Objective Fasting regimens can promote health, mitigate chronic immunological disorders, and improve age-related pathophysiological parameters in animals and humans. Several ongoing clinical trials are using fasting as a potential therapy for various conditions. Fasting alters metabolism by acting as a reset for energy homeostasis, but the molecular mechanisms underlying the beneficial effects of short-term fasting (STF) are not well understood, particularly at the systems or multiorgan level. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 103 publications
(119 reference statements)
0
5
0
Order By: Relevance
“…Unlike previous work which primarily focuses on circulating peripheral blood mononuclear cells and lymphocytes (Han et al, 2021;Huang et al, 2020), here we sorted CD45 + leukocytes cells to investigate both the differentials in innate and adaptive immune system. CD45 + cells are composed of myeloid, natural killer cells, T cells, B cells, and plasma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike previous work which primarily focuses on circulating peripheral blood mononuclear cells and lymphocytes (Han et al, 2021;Huang et al, 2020), here we sorted CD45 + leukocytes cells to investigate both the differentials in innate and adaptive immune system. CD45 + cells are composed of myeloid, natural killer cells, T cells, B cells, and plasma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, long-term calorie restriction differentially modified the expression of innate and adaptive immunity mediators in the intestine with increased gene expression of most cytokines (Suárez-Souto et al, 2012). A recent study showed that short-term (2-22 h) incomplete fasting in mice has differential transient effects on multiple organs (Huang et al, 2020). There, the authors identified T-cell regulation as a central and prominent target of systemic modulations during short-term fasting.…”
Section: Introductionmentioning
confidence: 99%
“…The manner by which extracellular signals are integrated and translated in cells to produce a coherent response is poorly understood. Here, we investigated the hepatic fasting response which is heavily reliant on transcriptional regulation ( 14 , 23 , 58 ). This response is controlled by the combinatorial effect of several signals, chief among them are glucagon and glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…The brain and liver bidirectionally communicate via humoral and neural networks ( 177 , 178 ). The neural axis between brain and liver interacts closely with the central nervous system (CNS) via the autonomic nervous system (ANS).…”
Section: Extrahepatic Factors and Hepatic Immune Regulationmentioning
confidence: 99%